1992
DOI: 10.1164/ajrccm/145.5.1129
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Maternal Smoking during Pregnancy on Early Infant Lung Function

Abstract: We studied the effect of prenatal maternal cigarette smoking on the pulmonary function (PF) of 80 healthy infants tested shortly after birth (mean, 4.2 +/- 1.9 wk). Mothers' prenatal smoking was measured by: (1) questionnaire reports at each prenatal visit of the number of cigarettes smoked per day, and (2) urine cotinine concentrations (corrected for creatinine) obtained at each visit. Infant PF was assessed by partial expiratory flow-volume curves and helium-dilution measurement of FRC. Forced expiratory flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
280
4
10

Year Published

1996
1996
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 499 publications
(314 citation statements)
references
References 13 publications
20
280
4
10
Order By: Relevance
“…ETS exposure in children is associated with lower FEV1 values compared to matched unexposed children [86]. Antenatal maternal smoking has been associated with a reduction in early-life lung function suggesting that in utero smoke exposure may affect airway development and lung elasticity [87]. Maternal smoking during pregnancy and in early life is the most significant source of exposure affecting infant lung function [85].…”
Section: Resultsmentioning
confidence: 99%
“…ETS exposure in children is associated with lower FEV1 values compared to matched unexposed children [86]. Antenatal maternal smoking has been associated with a reduction in early-life lung function suggesting that in utero smoke exposure may affect airway development and lung elasticity [87]. Maternal smoking during pregnancy and in early life is the most significant source of exposure affecting infant lung function [85].…”
Section: Resultsmentioning
confidence: 99%
“…The accurate assessment of fetal exposure to smoking through the objective measure of a biomarker could be of major importance for the investigation of the effects of preand postnatal environmental exposures to pollutants, including tobacco smoke, in the inception of respiratory diseases (Hanrahan et al, 1992;Nafstad et al, 1996Nafstad et al, , 1997Corbo et al, 1996;Lodrup Carlsen et al, 1997;Cook and Strachan, 1998;Strachan and Cook, 1998). Recently, we showed that cord serum cotinine resulted as the most adequate biomarker of fetal exposure to smoking at the end of pregnancy, distinguishing not only active smoking from passive smoking, but also exposure to environmental tobacco smoke (ETS) from nonexposure .…”
Section: Introductionmentioning
confidence: 99%
“…The most studied in utero environmental influence on lung development is maternal smoking in pregnancy, which has been shown to be associated not only with wheezing in childhood (2)(3)(4)(5) but also with a dose-related reduction in lung function in the newborn period. Fetal development seems therefore to represent a critical time of pulmonary vulnerability with respect to smoking exposure.…”
mentioning
confidence: 99%